2014
DOI: 10.1097/mpg.0000000000000468
|View full text |Cite
|
Sign up to set email alerts
|

National Trends and Outcomes of Pediatric Gastrostomy Tube Placement

Abstract: Surgical gastrostomy insertion rates have increased whereas PEG rates have not, despite evidence of better severity-adjusted outcome measures for PEG tubes. Surgical gastrostomy insertion in children <1 year of age yielded the greatest increase, which may relate to a changing patient population; however, regional variation suggests that provider preference also plays a role. Our data underline the need for more robust collection and analysis of surgical outcomes to guide decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
59
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 28 publications
8
59
0
1
Order By: Relevance
“…Among the patients who had medical hardware prior to presentation, g-tubes were the most common. A recent study found that g-tubes were performed at a fairly high rate, 18.5/100,000 US children in 2009 [5]. This supports the notion that the reason why g-tubes are the most common medical hardware noted during a failure to rescue event is because they occur in a higher number of pediatric patients compared to other types of medical hardware.…”
Section: Discussionsupporting
confidence: 59%
“…Among the patients who had medical hardware prior to presentation, g-tubes were the most common. A recent study found that g-tubes were performed at a fairly high rate, 18.5/100,000 US children in 2009 [5]. This supports the notion that the reason why g-tubes are the most common medical hardware noted during a failure to rescue event is because they occur in a higher number of pediatric patients compared to other types of medical hardware.…”
Section: Discussionsupporting
confidence: 59%
“…8, 9, 11 There has been an increasing trend to continue to feed children by mouth in an effort to avoid the morbidity of g-tubes, which often includes not only potential mechanical complications from the tube itself (e.g. skin infections, tube dislodgement) but potential worsening of gastroesophageal reflux or development of prolonged oral aversions preventing patients from weaning off their g-tube feeds.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrostomy tubes (g-tubes) are frequently used in order to allow for additional enteral access in patients with aspiration, including those thought to be at risk of having respiratory complications. 8-11 Prior data have suggested that for children with neurologic disability, g-tube placement may improve respiratory outcomes, including decreased antibiotic use and respiratory related hospitalizations. 12 Conversely, additional studies have shown that once placed, g-tubes are often fraught with complications, ranging from the minor (tube leakage, skin irritation, or formation of granulation tissue formation) to the more severe (worsening gastroesophageal reflux disease, g-tube cellulitis, or g-tube dislodgement).…”
mentioning
confidence: 99%
“…Some patients were classified as having multiple categories of comorbidities 2. American Society of Anesthesiologist (ASA) physical status classification system: ASA Class I, healthy person; ASA Class II, mild systemic disease; ASA Class III, severe systemic disease; ASA Class IV, severe systemic disease with a constant threat to life.…”
mentioning
confidence: 99%